Short-term impact of glycaemic control and intravitreal ranibizumab treatment on serum cytokine levels and diabetic macular edema in patients with unregulated blood glucose - Hürkan Kerimoğlu; İbrahim Kılınc; Bülent Savut; Mustafa Kulaksızoğlu; Günhal Şatırtav; Gülfidan Bitirgen; Emine Tınkır Kayıtmazbatır (Genel Tıp Dergisi)
Objective: To evaluate the short-term effect of glycaemic control and intravitreal ranibizumab treatment on diabetic macular edema (DME) and to assess the correlation between HbA1c and certain serum cytokines. Design: A prospective study of 43 participants with HbA1c levels exceeding 53 mmol/mol (7%) and with DME, as detected by spectral domain optical coherence tomography (SDOCT). Subjects: Participants were grouped according to their initial best corrected distance visual acuity (BCVA). Group 1 was treated with three monthly doses of intravitreal ranibizumab (0.5 mg) injections, and Group 2 was followed without treatment. Methods: Serum cytokine levels, including interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor-alpha (TNF-α), monocyte chemoattractant protein-1(MCP-1), and vascular endothelial growth factor (VEGF) were analysed at the beginning and at the end of 3 months, using enzyme-linked immunosorbent assays (ELISA). Results: A significant decrease in macular thicknesses (except for one quadrant) was observed in Group. Changes in serum cytokine levels were not correlated with HbA1c decrease. Serum VEGF level was significantly increased in Group 1, despite the intravitreal treatment. Conclusion: Short-term glycaemic control alone had limited value in the treatment of DME. The therapeutic effect of intravitreal treatment on DME supports the role of the local cytokine milieu in the pathophysiology.